The Role of Alcohol in Initial Help-Seeking Telephone Calls About Domestic Violence to the Police - Richardson, Emma (Violence against women, 2025)
This article investigates how domestic violence and abuse (DVA), its underreporting and its links with alcohol consumption, manifest in and impact the outcome of help-seeking telephone calls to U.K.-based police services. Conversation analysis of call-takers’ questions about alcohol found that they either (a) focused only on the perpetrator's drinking, and occurred after informing callers that help was being dispatched, or (b) targeted both victims’ and perpetrators’ drinking and complicated the decisions to dispatch police assistance. The article helps specify the communicative practices that may constitute victims’ negative experiences of disclosing DVA to the police.